Informed reasoning: repositioning of nitisinone to treat oculocutaneous albinism - Manga, Prashiela (American Society for Clinical Investigation, 2011)
Oculocutaneous albinism (OCA) is a group of genetic disorders characterized by hypopigmentation of the skin, hair, and eyes. Affected individuals experience reduced visual acuity and substantially increased skin cancer risk. There are four major types of OCA (OCA1–OCA4) that result from disruption in production of melanin from tyrosine. Current treatment options for individuals with OCA are limited to attempts to correct visual problems and counseling to promote use of sun protective measures. However, Onojafe et al., reporting in this issue of the JCI, provide hope for a new treatment approach for OCA, as they demonstrate that treating mice that model OCA-1b with nitisinone, which is FDA approved for treating hereditary tyrosinemia type 1, elevates plasma tyrosine levels, and increases eye and hair pigmentation.